PENILAIAN RISIKO LINGKUNGAN DAN INVESTASI PADA PERENCANAAN PELABUHAN KIJING, KALIMANTAN BARAT - Prabowomukti, Adhitya Reddia; Muchlis , Muchlis (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to identify environmental risks and assess the investment risk of the Port of Kijing. Data collection techniques in this study by conducting a field survey to PT. Pelabuhan Indonesia II branch office in Pontianak, surveying the conditions of meterology and oceanography in the Kijing area and also along the Kapuas River from upstream to downstream to find out the barge connectivity path. The next method is to conduct in-depth interviews with the Head of the Port of Pontianak, several shipping companies (ship logistics companies) and also Crude Palm Oil (CPO) producers related to throughput and ship traffic in Kalimantan. Based on the results of the study it can be concluded as follows: 1)The most common environmental risk events that occur are increasing noise and pollution around the port construction area. The highest level of risk that could potentially be fatal, or extreme risk, namely when the ship collided or touched. While the lowest risk level is if the terminal processing is delayed, 2) The overall investment risk assessment shows that the Kijing Port project has high potential in profitability and healthy cash flow performance, indicated by an Internal Rate of Return (IRR)of 13.3% and a positive Net Present Value (NPV) on a discount rate of 12%, so this investment is considered feasible.